Rehabilitacion de un paciente con acv que presenta marcha Guadañante - Rassa Iglesias, Dennis Andres (2017)
Stroke (stroke) can lead to scaling. In this work, the use of hot chemical compresses, low frequency currents, active mobility of the lower limbs assisted by the physiotherapist, the Brunnstrom facilitation technique, postural control through maintenance and recovery of stability as well as balance in different positions, it was possible to physically rehabilitate a patient with the diagnosis of spastic hemiplegia of the left hemisphere caused by a stroke. From the analysis of this case, protocols could be designed for the physiotherapeutic rehabilitation of elderly patients with hemiplegia caused by stroke, which will allow them to increase their quality of life and their family and social insertion.